Daerah Pasca Bencana, Daya Tarik Tersendiri bagi Pariwisata Indonesia - Elly Suhartini; Jati Arifiyanti (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract The events of natural disasters and the beauty of nature are two very popular things, not only in Indonesia but also around the world. Disaster is a tragedy for human life. Although the memories must be remembered and respected, the location of the disaster can also be used as tourist destinations. The area after the natural disaster becomes the main attraction for the tourists. This article to give an idea of the area after the disaster does not mean that there has been destruction and devastation. But the area can still be repaired and developed again into a tourist destination. The disaster affected areas are presenting a new uniqueness and something that can be sold as a tourist destination with a new natural product. The tourist destination becomes a tourism commodity due to the uniqueness / peculiarities of nature and / or culture around it, in addition to the factor of self-reflection and contemplation of events in the past. Disaster-affected areas should be rebuilt with the spirit of creativity and the attention of various parties who are able to see the opportunities gap unique tourism. Keywords: Natural disaster, tourist attraction, Indonesian tourism